'Guilty, no doubt': detention provoking confirmation bias in judges' guilt assessments and debiasing techniques. Issue 3 (16th March 2019) - Lidén, Moa; Gräns, Minna; Juslin, Peter
ABSTRACT: This research examines whether judges' pretrial detention decisions trigger confirmation bias in their guilt assessments. It also tests two strategies to mitigate confirmation bias: (1) to have different judges decide about detention and guilt and (2) to reduce cognitive load by structuring the evaluation of evidence. In Experiment 1, Swedish judges ( N  = 64) read 8 scenarios in which they either decided themselves about detention or were informed about a colleague's decision. Then, participants rated the defendant's trustworthiness, the strength of each piece of evidence, the total evidence and decided about guilt. In Experiment 2, Law students ( N  = 80) either first rated each piece of evidence separately and then the total evidence (structured evaluation) or only the total evidence (unstructured evaluation), and then decided about guilt. Overall, detained defendants were considered less trustworthy and when participants themselves detained, they rated the guilt consistent and total evidence as stronger and were more likely convict, compared to when a colleague had detained. The total evidence was considered stronger after unstructured than structured evaluations of the evidence but the evaluation mode did not influence guilt decisions. This suggests that changing decision maker holds greater debiasing potential than structuring evidence evaluation.